Ball trajectories in tennis - Lateral and vertical placement of right handed men's singles serves - Kolbinger, O.; Lames, M. (International Journal of Performance Analysis in Sport, 2013)
The aim of the study was to investigate the distribution of tennis serves in a more accurate and more tennis-specific way than previous studies. In order to do that, the y-z-coordinates when the ball is level with the receiver were calculated based on a model with data obtained by Hawk-Eye technology for 10418 serves of 53 right handed male players on hard court. Two way repeated measures ANOVAs showed significant differences for lateral and vertical distributions between serves from the ad court and from the deuce court, as well as for first and second serves. First serves lateral distribution was M-shaped, but apparently independent of tactical intentions towards the opponent, whereas second serves are placed more frequently on the backhand-side of the receiver. Furthermore, the second serves pass show a higher trajectory. Thus the results of the study also confirmed the necessity of including the z-coordinate in investigations on service placement in tennis.